2015
DOI: 10.1111/ocr.12102
|View full text |Cite
|
Sign up to set email alerts
|

A finite element analysis of the maxillary first molar PDL with maxillary protraction in a mixed dentition Class III malocclusion

Abstract: The suggested orthodontic movement is in the mesial direction with a small amount of extrusion with 15° angulation and greater extrusion with 30° and 45°.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…It is known that biomechanical models of the human TMJ are not perfect, rather they are based on a number of assumptions and simplifications. More specifically, biomechanical model could not mimic the influence of different cytokines such as IL-4, IL-6, and IL-12 [33][34][35]. In future studies, we aim to determine the nutrient environment in TMJ discs by using combined experimental and computational modelling approaches.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that biomechanical models of the human TMJ are not perfect, rather they are based on a number of assumptions and simplifications. More specifically, biomechanical model could not mimic the influence of different cytokines such as IL-4, IL-6, and IL-12 [33][34][35]. In future studies, we aim to determine the nutrient environment in TMJ discs by using combined experimental and computational modelling approaches.…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 and its signaling pathway appear to be a potential therapeutic target for cancer. Interestingly, a recent research demonstrated that PD-L1 expression had the capability to change over time with anti-PD-L1 antibody therapy [ 33 ]. Therefore, its expression status of a specific tumor tissue may not reflect the present immunologic phenotype of tumor.…”
Section: Chemotherapy Alters the Expression Of Pd-1/pd-l1mentioning
confidence: 99%
“…In a 3D FEA model of a tooth‐periodontium system with complicated geometry, it is convenient to apply mechanical forces at any regions and in any directions . FEA has provided essential new knowledge for tooth restoration , prosthetic and orthodontic treatment , implant design , tooth fracture and periodontal trauma analysis, as well as the biomechanics of the mandibular system .…”
Section: Introductionmentioning
confidence: 99%